Energetic material, preparation thereof and application of energetic material as explosive and spontaneous combustion type propellant
By developing the new energy-containing material MIC12H12N10 or MⅡC8H6N8, the reaction method of sodium dicyandiamide, imidazole ligand and metal salts is used to solve the shortcomings of existing self-ignition propellants in terms of energy density and storage and transportation, and achieve high energy density and good stability performance improvement, suitable for high-performance explosives and propellants.
Patent Information
- Application Number
- CN202411685615.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-23
AI Technical Summary
The existing spontaneous combustion propellants have shortcomings in energy density and storage and transportation, and it is difficult to meet the demand for propellants with better performance in aerospace technology.
A new energy-containing material was developed with the chemical formula of MIC12H12N10 or MⅡC8H6N8, and was prepared by reaction method of sodium dicyandiamide, imidazole ligand and metal salt, with high energy density and good stability.
The energy density of the energy-containing material prepared is significantly higher than that of the existing hydrazine-type self-ignition propellants, with thermal stability ≥130 ℃, excellent impact sensitivity, friction sensitivity, volume energy density and specific impulse performance, suitable for explosives and self-ignition Propeller.
Smart Images

Figure CN119490541A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energetic materials, and in particular relates to a new type of energetic material and a preparation method thereof, and the application of the material in the field of explosives and self-igniting propellants. Background Art
[0002] Energetic materials play a vital role in key areas such as explosives, propellants and pyrotechnics. Although the hypergolic propellants currently on the market, such as hydrazine and its derivatives, nitrogen tetroxide and liquid oxygen-kerosene, have advantages in synthesis process and cost, they have obvious shortcomings in energy density and storage and transportation. With the continuous advancement of aerospace technology, the demand for hypergolic propellants with better performance is becoming increasingly urgent. At the same time, solid fuel engines, as an emerging technology, are gradually receiving widespread attention from the industry. Although research on solid fuels is still in its early stages, its potential in improving energy density and simplifying storage and transportation processes has already emerged. Therefore, the development of commercial solid hypergolic propellants with high performance has become an important and urgent research direction in the field of energetic materials. Summary of the invention
[0003] The purpose of the present invention is to provide a class of energetic materials and a preparation method thereof and their application as explosives and hypergolic propellants. The energy density of the energetic material is much higher than that of the currently commercially available hydrazine hypergolic propellants, and the energetic material is simple to synthesize and easy to store and transport, thus being a high-performance energetic material.
[0004] To achieve the above object, the present invention adopts the following technical solution: One of the purposes of the present invention is to protect a class of energetic materials having the chemical formula M I C 12 H 12 N 10 or M Ⅱ C8H6N8, among which, M I One selected from Co, Ni, Cu; M Ⅱ Selected from Zn.
[0005] For the chemical formula M 1 C 12 H 12 N 10 energetic material, as an embodiment, when M I When selected from Co, its crystal structure is monoclinic and the space group is I2 / a , the unit cell parameters are a =15.1244~15.1258 Å, b =7.3091~7.3096 Å, c =14.9704~14.9718 Å, α=90.00°, β =110.393~110.404°, γ =90.00°, Z =4.
[0006] For the chemical formula M 1 C 12 H 12 N 10 energetic material, as an embodiment, when M I When selected from Ni, its crystal structure is monoclinic and the space group is C2 / c , the unit cell parameters are a =17.0631~17.0642 Å, b =7.2272~7.2274 Å, c =14.9584~14.9594 Å, α =90.00°, β =125.523~125.532°, γ =90.00°, Z =4.
[0007] For the chemical formula M 1 C 12 H 12 N 10 energetic material, as an embodiment, when M I When selected from Cu, its crystal structure is triclinic, and the space group is P-1 , the unit cell parameters are a =7.6794~7.6796 Å, b =8.9293~8.9295 Å, c =11.8172~11.8173 Å, α =93.5190~93.5200°, β =95.7540~95.7550°, γ =106.672~106.674°, Z =2.
[0008] For the chemical formula M Ⅱ The energetic material of C8H6N8, as an embodiment, when M Ⅱ When selected from Zn, its crystal structure is monoclinic and the space group is P2 1 / c , the unit cell parameters are a =13.2102~13.2115 Å, b =11.8863~11.8873 Å, c=7.5328~7.5334 Å, α =90.00°, β =94.534~94.543°, γ =90.00°, Z =4.
[0009] Furthermore, the thermal stability of the energetic material is ≥130°C.
[0010] Furthermore, the impact sensitivity of the energetic material is ≥40 J.
[0011] Furthermore, the friction sensitivity of the energetic material is ≥360N.
[0012] Furthermore, the volume energy density of the energetic material is ≥30 kJ·cm −3 .
[0013] Furthermore, the specific impulse of the energetic material is ≥210 s.
[0014] The second object of the present invention is to protect the preparation method of the energetic material, and the reaction formula is as follows: .
[0015] Specifically, the energetic material is prepared by dissolving sodium dicyanamide (NaDCA) and imidazole ligands in water, and slowly dropping a mixture containing M I or M Ⅱ The aqueous solution of the metal salt of the element is reacted, filtered, and placed in the air for several days to crystallize to obtain the product. The method has simple steps, high purity and high yield, and is suitable for large-scale industrial production.
[0016] Further, the used sodium dicyandiamide, imidazole ligand and the containing M I or M Ⅱ The molar ratio of the metal salts of the elements is 2:2:1.
[0017] Furthermore, the imidazole ligand is 2-methylimidazole (2-Mim).
[0018] Furthermore, the metal salt is a nitrate, chloride, sulfate or bromide of the corresponding metal element.
[0019] Furthermore, the reaction temperature is room temperature and the reaction time is 0.5-1 hour. In operation, those skilled in the art can select appropriate reaction time and reaction temperature according to actual needs, subject to the reaction being fully carried out.
[0020] Furthermore, the obtained energetic material can be a large block single crystal or a crystal powder.
[0021] A third object of the present invention is to protect the application of the energetic material.
[0022] One aspect of the application is to provide an explosive containing any of the above energetic materials and at least one of the energetic materials prepared by any of the above methods.
[0023] Another aspect of the application is to provide a hypergolic propellant, which contains at least one of any of the above energetic materials and energetic materials prepared by any of the above methods.
[0024] The beneficial effects of the present invention include but are not limited to: (1) The present invention provides a new type of energetic material. The energetic material has excellent stability and safety. Experimental determination shows that its thermal stability is ≥130 °C, its impact sensitivity is ≥40 J, its friction sensitivity is ≥360 N, and its volume energy density is ≥30 kJ·cm −3 , specific impulse ≥ 210 s. The energy density of the energetic material provided by the present invention significantly exceeds that of the hydrazine-nitrogen tetroxide propellants currently commercialized on the market. It not only achieves a major breakthrough in energy release efficiency, but also overcomes the problem of increased internal pressure in the fuel tank caused by continuous evaporation of hydrazine hypergolic propellants during storage, as well as the inconvenience of liquid fuel in storage and transportation. These innovative characteristics make the present invention have significant commercial application value in the field of high-performance energetic materials, indicating great potential in aerospace propulsion technology and related industrial applications.
[0025] (2) The present invention provides a method for preparing the energetic material. The method has simple steps, and the obtained energetic material has high purity, good crystallinity and high yield, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Sample P1 prepared in Example # -P4 # Theoretical XRD diffraction pattern obtained by fitting single crystal data and its experimentally measured XRD diffraction pattern.
[0027] Figure 2 Sample P1 prepared in Example # -P4 # Schematic diagram of the crystal structure (without hydrogen atoms), where (a) P1 # , (b) P2 # , (c) P3 # , (d) P4 # .
[0028] Figure 3 Sample P1 prepared in Example # -P4 # Ignition delay time test diagram. DETAILED DESCRIPTION
[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0030] Example 1 CoC 12 H 12 N 10 Preparation Dissolve 178 mg sodium dicyandiamide and 164 mg 2-methylimidazole in water, then slowly drop an aqueous solution containing 155 mg CoSO4 into the mixture. After reacting at room temperature for 30 minutes, filter and evaporate in the air for several days to obtain CoC 12 H 12 N 10 Red crystals, labeled P1 # .
[0031] Example 2 NiC 12 H 12 N 10 Preparation Dissolve 178 mg sodium dicyandiamide and 164 mg 2-methylimidazole in water, then slowly drop 238 mg NiCl2·6H2O aqueous solution into the mixture, react at room temperature for 30 minutes, filter, and evaporate in the air for several days to obtain NiC 12 H 12 N 10 Green crystals, labeled P2 # .
[0032] Example 3 CuC 12 H 12 N 10 Preparation Dissolve 178 mg of sodium dicyandiamide and 164 mg of 2-methylimidazole in water, then slowly drop 170 mg of CuCl2·2H2O aqueous solution into the mixture, react at room temperature for 30 minutes, filter, and evaporate in the air for several days to obtain CuC 12 H 12 N 10 Blue crystals, labeled P3 # .
[0033] Example 4 Preparation of ZnC8H6N8 Dissolve 178 mg sodium dicyandiamide and 164 mg 2-methylimidazole in water, then slowly drop an aqueous solution containing 225 mg ZnBr2 into the mixture. After reacting at room temperature for 30 minutes, filter and evaporate in the air for several days to obtain white crystals of ZnC8H6N8, marked as P4 # .
[0034] Structural characterization of samples Sample P1 # ~P4 # The X-ray powder diffraction phase analysis (XRD) of the ground samples was carried out on a Rigaku MiniFlex600 X-ray diffractometer with a Cu target, a Kα radiation source (λ = 0.1540598 nm), a voltage of 40 kV, a current of 20 mA, and a test angle of 2. θ Range 5~50°, test speed 5° per minute. At the same time, sample P1 # ~P4 # X-ray single crystal diffraction was carried out on a Mercury CCD single crystal diffractometer with a Mo target and a Kα radiation source (λ = 0.07107 nm) at a test temperature of 100 ~ 298 K, and the structure was roughly solved by SHELXTL.
[0035] The XRD diffraction spectrum obtained by fitting the single crystal data is compared with the experimental XRD diffraction spectrum. Figure 1 As shown. Figure 1 It can be seen that the XRD diffraction pattern obtained by fitting the single crystal data is highly consistent with the experimentally measured XRD diffraction pattern, proving that the obtained sample is a sample of high purity and high crystallinity.
[0036] P1 # ~P4 # The unit cell parameters are shown in Table 1, and the crystal structure diagram is shown in Figure 2 As shown. Figure 2 It can be seen that among the four compounds, the imidazole ligand adopts a monodentate coordination mode, while the dicyandiamide ion chooses a bidentate coordination mode between the nitrogen atoms at both ends and the metal center and a monodentate coordination mode. # 、P2 # The hexacoordinate structure is shown, P3 # It is a five-coordinate structure, P4 # It is a four-coordinate structure. All structures are one-dimensional chain structures.
[0037] Specifically, P1 # The structural analysis of P1 # In the monoclinic space group I2 / a Crystallographic asymmetric unit contains half of MI Center, a 2-Mim ligand and a DCA - Anion. M I The center consists of two 2-Mim ligands and four DCAs − The anion is hexacoordinated to provide a distorted octahedron. The neutral ligand 2-Mim is distributed on both sides of the main chain by terminal coordination. - The stretching of anions in the horizontal plane forms a one-dimensional long-chain polymer structure using the bridging coordination modes of μ2-κN21:κN23 and μ2-κN21#2:κN23#2. I Between b The distance between the axes is 7.31 Å. These one-dimensional chains stack via van der Waals forces, generating a three-dimensional supramolecular network.
[0038] Similarly, P2 # Shown with P1 # Similar coordination environment and stacking mode, in the monoclinic space group C2 / c Medium crystallization, with the characteristics of a one-dimensional chain.
[0039] P3 # In the triclinic space group P-1 According to the single crystal X-ray diffraction analysis data, it belongs to a non-periodic structure. I Center, two DCAs - The anion and two 2-Mim ligands constitute the basic asymmetric unit. I The coordination environment of the center is a penta-coordinate mode, with the 2-Mim ligand and two nitrogen atoms forming a distorted triangle. In addition, a DCA with μ2-κN31:κN33 coordination mode - Anions are the linking molecules of adjacent M I The one-dimensional chain is connected by van der Waals forces along the bc Staggered arrangement.
[0040] P4 # In the monoclinic space group P2 1 / c The asymmetric unit consists of an M Ⅱ Center, a 2-Mim ligand and two DCAs - Anion. Four-coordinated M Ⅱ The center is bound by a 2-Mim ligand and three DCAs - Anions surround. Part of DCA - The anion exhibits terminal coordination, while the other anions exhibit bridging coordination through the two terminal nitrogen atoms, similar to compound P3# These one-dimensional structures are connected by van der Waals forces along bc Stacking to form a regularly alternating network structure.
[0041] Table 1 M I C 12 H 12 N 10 (M I = Co, Ni, Cu) and M Ⅱ C8H6N8(M Ⅱ = Zn) related crystallographic parameters
[0042] 2. Sensitivity test and dripping test For sample P1 # ~P4 # The friction sensitivity experiment was conducted with the following specific steps: According to the national military standard for energetic materials, the BAM sensitivity tester FSKM-10 produced by the Czech OZM company was used to determine the value corresponding to the 50% ignition rate of the compound through dozens of tests.
[0043] The oxidant used in the drop test is 98% fuming nitric acid, the sample mass is about 10 mg, the drop height is about 25 cm, and the value of the compound ignition delay time is determined through more than five tests. The delayed ignition times are 39 ms, 70 ms, 65 ms, and 100 ms respectively.
[0044] Sample P1 # ~P4 # The experimental data of energetic properties are shown in Table 2.
[0045] Table 2 M I C 12 H 12 N 10 (M I = Co, Ni, Cu) and M Ⅱ C8H6N8(M Ⅱ = Zn) related performance parameters
[0046] It can be seen from the above experimental results that the thermal stability of the energetic material provided by the present invention is not less than 130 °C, the impact sensitivity is ≥40 J, the friction sensitivity is ≥360 N, and the volume energy density is not less than 30 kJ·cm −3 The specific impulse is not less than 210 s, the ignition delay time is as short as 39 ms, and the energy density is much higher than the currently commercially available hydrazine hypergolic propellant. It is a new type of energetic material with excellent performance and important commercial application value.
[0047] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A class of energetic materials, characterized in that: The chemical formula of the energetic material is M I C 12 H 12 N 10 or M Ⅱ C8H6N8, among which, M I One selected from Co, Ni, Cu; M Ⅱ Selected from Zn.
2. The energetic material according to claim 1, characterized in that For the chemical formula M 1 C 12 H 12 N 10 energetic materials, when M I When selected from Co, its crystal structure is monoclinic and the space group is I2 / a , the unit cell parameters are a =15.1244~15.1258 Å, b =7.3091~7.3096 Å, c =14.9704~14.9718 Å, α =90.00°, β =110.393~110.404°, γ =90.00°, Z =4; When M I When selected from Ni, its crystal structure is monoclinic and the space group is C2 / c , the unit cell parameters are a =17.0631~17.0642Å, b =7.2272~7.2274 Å, c =14.9584~14.9594 Å, α =90.00°, β =125.523~125.532°, γ =90.00°, Z =4; When M I When selected from Cu, its crystal structure is triclinic, and the space group is P-1 , the unit cell parameters are a =7.6794~7.6796 Å, b =8.9293~8.9295 Å, c =11.8172~11.8173 Å, α =93.5190~93.5200°, β =95.7540~95.7550°, γ =106.672~106.674°, Z =2.
3. The energetic material according to claim 1, characterized in that For the chemical formula M Ⅱ Energetic materials of C8H6N8, when M Ⅱ When selected from Zn, its crystal structure is monoclinic and the space group is P2 1 / c , the unit cell parameters are a =13.2102~13.2115Å, b =11.8863~11.8873 Å, c =7.5328~7.5334 Å, α =90.00°, β =94.534~94.543°, γ =90.00°, Z =4.
4. The energetic material according to claim 1, characterized in that The thermal stability of the energetic material is ≥130 °C; the impact sensitivity is ≥40 J; the friction sensitivity is ≥360 N; and the volume energy density is ≥30 kJ·cm −3 ; Specific impulse ≥ 210 s.
5. A method for preparing an energetic material according to claim 1, characterized in that: Dissolve sodium dicyandiamide and imidazole ligands in water and slowly drip the mixture containing M I or M Ⅱ The aqueous solution of metal salts of elements is reacted, filtered, and evaporated in the air to obtain the result.
6. The method for preparing energetic materials according to claim 5, characterized in that: The imidazole ligand is 2-methylimidazole.
7. The method for preparing an energetic material according to claim 5, characterized in that: The molar ratio of the used sodium dicyandiamide, imidazole ligand and metal salt is 2:2:
1.
8. The method for preparing an energetic material according to claim 5, characterized in that: The reaction temperature is room temperature and the reaction time is 0.5-1 hour.
9. An explosive, characterized in that: Contains at least one of the energetic materials described in any one of claims 1 to 4 and the energetic materials prepared by the method described in claims 5 to 8.
10. A hypergolic propellant, characterized in that: Contains at least one of the energetic materials described in any one of claims 1 to 4 and the energetic materials prepared by the method described in claims 5 to 8.
Citation Information
Patent Citations
Energy-containing material, preparation method thereof and application of energy-containing material as initiating explosive, explosive and pyrotechnic compound
CN107674099A
Dicyandiamide transition metal salt and preparation method thereof
CN110563001A
Inorganic-organic hybrid compound crystal, preparation method thereof and application of inorganic-organic hybrid compound crystal as energetic material
CN114907411A
Crystal material, synthetic method thereof, energetic material and application
CN116856063A
Propellant for gas generators
US20030145923A1